2014
DOI: 10.1155/2014/237034
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of 0.1% Ropivacaine-Fentanyl with 0.1% Bupivacaine-Fentanyl Epidurally for Labour Analgesia

Abstract: Ropivacaine is an alternative to epidural bupivacaine, with greater selectivity for sensory fibres than motor fibres, thus producing less motor blockade as compared to bupivacaine. The purpose of this study was to evaluate the efficacy of Ropivacaine 0.1% when administered epidurally for the relief of labour pain and to compare it with 0.1% bupivacaine, conducted at Rajindra Hospital Patiala, Baba Farid University of Health and Sciences, on 20 parturients after ethical approval from the institutional review bo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 12 publications
(9 reference statements)
1
4
0
Order By: Relevance
“…Our findings regarding neonatal outcomes were comparable with the literature ( 4 , 13 , 14 , 15 , 16 ) . There were no significant differences in the indicators of neonatal wellbeing between the two groups.…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…Our findings regarding neonatal outcomes were comparable with the literature ( 4 , 13 , 14 , 15 , 16 ) . There were no significant differences in the indicators of neonatal wellbeing between the two groups.…”
Section: Discussionsupporting
confidence: 91%
“…Shokry et al ( 18 ) compared two groups receiving 0.125% bupivacaine and 0.2% ropivacaine, each with fentanyl 100 µg and found an non-significant faster onset of action and significantly shorter duration of analgesia in the ropivacaine group. In contrast, Chora and Hussain ( 4 ) showed significantly faster onset of analgesia in the bupivacaine group and longer duration in the ropivacaine group. Unlike these, the onset and duration of analgesia for both groups was comparable in current study, consistent with the research of Beilin et al ( 19 ) .…”
Section: Discussionmentioning
confidence: 84%
See 2 more Smart Citations
“…We found that there was non-significant difference in MAP, MHR and FHR in group I and II at baseline and lowest value (P> 0.05). Chora et al, [9] observed that ropivacaine 0.1% and bupivacaine 0.1%, with fentanyl 20 μg/mL, produced equivalent analgesia for labour. There were no statistically significant differences in the amount of local anaesthetic used, pain scores, sensory levels, motor blockade, labour duration, mode of delivery, and side effects or patient satisfaction amongst the two local anaesthetics using the intermittent top-up technique.…”
Section: Discussionmentioning
confidence: 99%